Intersections of Gender, Caste and Environment: Amplifying Indigenous Voices in Ecofeminism. - CHERECHÉS, BIANCA (Atlantis (0210-6124), 2026)
Ongoing environmental degradation, rooted in capitalism and neo-colonialism, disproportionately impacts nature-dependent communities. In the Indian context, historical natural exploitation, initiated during colonial times and exacerbated post-independence through industrialisation, poses ecological threats to biodiversity and dispossesses tribal communities, also known as Adivasis. The complex interplay of caste, class and gender and their dependence on nature have further complicated the challenges that Adivasi women have had to confront. This paper will delve into Mahasweta Devi’s depiction of the exploitation of nature and its repercussions on tribal communities, particularly women, and will seek to emphasise how her narratives endeavour to shed light on the patriarchal foundations of capitalist development, as part of the environmental justice discourse. The short stories "Witch" (Bitter Soil, 1998) and "Douloti the Bountiful" (Imaginary Maps, 1995) will form the basis of the analysis, given the link made between environmental exploitation and the subjugation of Adivasi women in both. Ecofeminism is pivotal in grasping the intricate dynamics involved when women bear ecological impacts. However, the paper advocates for broadening the ecofeminist discourse through the lens of intersectionality, emphasising the interplay of diverse factors in shaping women’s identity. It ultimately proposes "intersectional ecofeminism" as a broader framework from which to approach the experiences of Indian tribal women and analyse how the intersection of caste, class, gender and ecology influences their identities and contributes to their marginalisation.